Analisis Korelasi Product Moment Dalam Menentukan Hubungan Kedisiplinan Mengajar Guru Pendidikan Agama Islam Dengan Kedisiplinan Belajar Siswa di Sekolah Menengah Pertama Negeri 2 Tandun - Efendi, Rahmi Maldini; Risnawati, Risnawati; Hamdani, M. Fikri (Peneliti.net, 2025)
This study aims to determine the relationship between the teaching discipline of Islamic Religious Education teachers with student learning discipline at State Junior High School 2 Tandun. This research is a type of correlation research with a quantitative approach. The population in this study was 237 people and a sample of 20% with a total of 47 people. Sample withdrawal using proported stratified random sampling technique, which is stratified or tiered in a balanced manner. Data collection using lift, documentation, and observation. Data analysis technique using product moment correlation test. Based on the results of data analysis, it is known that there is a significant and positive relationship between the discipline of teaching Islamic Religious Education teachers with student learning discipline at State Junior High School 2 Tandun, obtained the value of r_hitung> r_tabel which is 0.552> 0.288, with a significant level smaller than α (5%) which is 0.000 <0.05. Keywords: Teaching Discipline, Learning Discipline, Islamic Religious Education.